Motivasi Penggunaan Layanan Internet Banking dan Hubungannya dengan Perbedaan Gender - Sihotang, Ellen Theresia; Sekarsari, Larasati Ayu (Jurnal Manajemen dan Kewirausahaan, 2018)
This study aims to describe and analyze the motivations of using internet banking with gender as the moderation to representation the consumer behavior which can provide design of marketing strategies based on customersâ€™ desires and needs. The sampling techniques are a purposive and a snowball sampling with 250 respondents in Surabaya. The result shows that perceived of usefulness, perceived ease of use, perceived of security and bank initiatives are motivations that encourage using the internet banking service. However, gender as the moderation does not influence to all these factors in using internet banking services. Â https://doi.org/10.26905/jmdk.v6i2.2331